Social services for homeless people in Santa Cruz de Tenerife: an approach based on the Outreach model - Espinel-Camacho, Patricia; Díaz-González, José Manuel; Lorenzo-Alegría, Maryurena (Prospectiva. Revista de Trabajo Social e Intervención Social, 2026)
Homelessness represents one of the most extreme forms of social exclusion, resulting from the interaction of structural, institutional, relational, and individual factors. Mobile Outreach Units operate as key mechanisms for contact, engagement, and direct service delivery within the Outreach model. This article presents the results of a study carried out in Santa Cruz de Tenerife during 2023 to analyze the relationships between different types of care, to identify differences by sex, origin, type of Mobile Outreach Unit /UMA), use of housing resources and the presence of an Individualized Care Plan (PAI). It was also proposed to explore geographical variations, to identify user profiles according to the frequency and nature of interventions, as well as to examine seasonal trends in service provision. A quantitative, non-experimental, observational, descriptive, and retrospective study was carried out based on 450 service users and 28,416 recorded interventions. Nonparametric analyses, Spearman correlations, cluster analysis (k-means), and monthly trend analyses were applied following a rigorous process of debugging, categorizing, and verifying the consistency of records. The results showed that UMA 1 concentrated 73,7 % of attentions while UMA 2 concentrated 26,3 %. Positive correlations were observed between most of the actions, which demonstrated that the UAMs constitute an essential resource for social care in homelessness. The findings provide evidence to improve service planning and to tailor interventions from a gender-sensitive, intercultural, and intersectional perspective. Further mixed methods of research are recommended.